Mathematical results in quantum mechanics : proceedings of the QMath10 Conference, Moieciu, Romania, 10-15 September 2007 - Beltita, Ingrid; Nenciu, Gheorghe; Purice, R. (Radu), 1954- (World Scientific, 2008)
"This collection of carefully selected papers aims to reflect recent techniques and results on Schrodinger operators with magnetic fields, random Schrodinger operators, condensed matter and open systems, pseudo-differential operators and semiclassical analysis, quantum field theory and relativistic quantum mechanics, quantum information, and much more. The book serves as a concise and well-documented tool for the more experimented scientists, as well as a research guide for postgraduate students."--Jacket